PERLINDUNGAN HUKUM TERHADAP HAK-HAK EKSPORTIR DALAM PERMBAYARAN TRANSAKSI EKSPOR IMPOR MENGGUNAKAN OPEN ACCOUNT - Fikri Al Mansur; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Import and export is a form of economic relations between countries in the world. Import Export Transactions are simple international trade transactions which is buy and sell goods between entrepreneurs who are located in different countries. Exports are carried out by sellers in Indonesia, while imports by sellers abroad. So, import and export is the act of sell and buy by the seller to the buyer.In the practice of trading, most UMKM in Indonesia in international trade transactions use the open account payment method. The open account payment method was chosen because importers and exporters who have been trading for a relatively long time have known each other and have full mutual trust in the credibility of the importer, for exporters and importers payment method in this way is considered simple because it does not require varying documents, and reduces processing costs documents when compared to other payment methods.Open account payment method there is a risk for exporters, when the ordered goods have been sent to overseas buyers while the buyer does not make the payments for any reasons or the buyer is late in making payments causing losses for the exporter. Exporters depend entirely on financial flexibility, and the reputation of the importer to fulfill his obligations.The purpose of this study to find out how the legal protection of the rights of exporters who make payments for import export transactions using an open account and how to resolve the law if there is a breach of contract by the importer. The legal protection of the rights of exporters in payment of export and import transactions through an open account, at the initial stage of the transaction a sales contract is made, which contains state jurisdiction as the basis for choice of law in the event of a dispute. An empty law to organize the protection of exporters in payment of international trade transactions is an important homework for the government. Legal settlement in the breach of contract by the importer can be resolved peacefully, diplomatically (negotiation, fact finding, good services, mediation and conciliation) and by the law (International Arbitration and International Court of Justice).Keywords: Export, Import, Payment, Open Account.